Gaining Competitive Advantage in The European Pharmaeutical Generics Market - Dos Santos, Roberta; Allam, Dina; Murphy, John; Del Corral, Jose Alberto (2010)
The aim of this study is to examine the necessary elements of competitive advantage for a global pharmaceutical company as it embarks on its launch into 16 European generics market. The academic base explores five of Vargo and Lusch’s Service Dominant-logic foundational premises and the actions that must be taken for the company to move from a market to relational exchange level. The project is divided into two key deliverables, the first one being an environmental scanning to understand the market and hospital’s purchasing process, and the second one a further research into 4 main areas involved in the process of customer value creation. The environmental scanning includes assessment of external market factors and internal characteristics that provide a careful understanding of the business environment, its key decision makers, buying structure and the political nuances affecting the industry at large. This study tells the story of generic drugs from production to consumption, who to influence and how to do it. The second part explores four areas, three on the marketing literature and one on corporate social responsibility, all with the goal of identifying aspects to co-create value with hospital decision makers and to help PharmCo gaining competitive advantage through higher collaboration in between buyer and supplier. These include stakeholder analysis, trust and relationships building, customer value creation through enhanced product and service attributes, and sales force deployment and development. Final conclusions bundle the markets into archetypes, according to their similarities and requirements for value co-creation, and cross the results from the individual studies within the SD-logic foundational premises.